In vitro degradation and cell viability assessment of Zn-3Mg alloy for biodegradable bone implants - Dambatta, M.; Murni, N.; Izman, S.; Kurniawan, Denni; Froemming, G.; Hermawan, H. (Sage Publications, 2015)
© IMechE 2015. This article reports the in vitro degradation and cytotoxicity assessment of Zn-3Mg alloy developed for biodegradable bone implants. The alloy was prepared using casting, and its microstructure was composed of Mg2Zn11 intermetallic phase distributed within a Zn-rich matrix. The degradation assessment was done using potentiodynamic polarization and electrochemical impedance spectrometry. The cell viability and the function of normal human osteoblast cells were assessed using 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium and alkaline phosphatase extracellular enzyme activity assays. The results showed that the degradation rate of the alloy was slower than those of pure Zn and pure Mg due to the formation of a high polarization resistance oxide film. The alloy was cytocompatible with the normal human osteoblast cells at low concentrations ( < 0.5 mg/mL), and its alkaline phosphatase activity was superior to pure Mg. This assessment suggests that Zn-3Mg alloy has the potential to be developed as a material for biodegradable bone implants, but the toxicity limit must be carefully observed.